2013
DOI: 10.3399/bjgp13x660814
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of empathy in general practice: a systematic review

Abstract: Although only a small number of studies could be used in this search, the general outcome seems to be that empathy in the patient-physician communication in general practice is of unquestionable importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
546
7
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(595 citation statements)
references
References 63 publications
12
546
7
30
Order By: Relevance
“…Studi menunjukkan bahwa empati dokter kepada pasien meningkatkan akurasi diagnostik, meningkatkan pemahaman pasien terhadap kondisi penyakitnya, meningkatkan kepatuhan pasien terhadap pengobatan, meningkatkan kepuasan dan kualitas hidup serta menurunkan stres pada pasien. 5,6,7 Penemuan terakhir juga menunjukkan bahwa empati dokter kepada pasien dapat mempengaruhi kondisi imunitas pasien terhadap common cold melalui perubahan interleukin-8. 5 Manfaat empati dalam komunikasi dokter-pasien tidak didukung oleh realitas.…”
Section: Pendahuluanunclassified
“…Studi menunjukkan bahwa empati dokter kepada pasien meningkatkan akurasi diagnostik, meningkatkan pemahaman pasien terhadap kondisi penyakitnya, meningkatkan kepatuhan pasien terhadap pengobatan, meningkatkan kepuasan dan kualitas hidup serta menurunkan stres pada pasien. 5,6,7 Penemuan terakhir juga menunjukkan bahwa empati dokter kepada pasien dapat mempengaruhi kondisi imunitas pasien terhadap common cold melalui perubahan interleukin-8. 5 Manfaat empati dalam komunikasi dokter-pasien tidak didukung oleh realitas.…”
Section: Pendahuluanunclassified
“…It has been shown that physicians who can empathize with their patients provide better care than those who are unable to empathize (Eikeland et al 2014;Derksen et al 2013;Di Blasi and Kleijnen 2003;Halpern 2001;Hojat et al 2011Hojat et al , 2013Hooker 2015;Pedersen 2008;Roter et al 1998). Empathy greatly enhances the physician-patient interaction, allowing for the physician to better understand the patient's experiences, and therefore better understand how the patient should be treated.…”
Section: The Benefits Of Empathy For Patients and Physiciansmentioning
confidence: 99%
“…Additionally, empathy decreases patient anxiety and allows them to feel empowered (Derksen et al 2013;Halpern 2014, p. 303). Patients feel like they are part of the medical encounter, that their input matters, and that they have a say in what will happen to them.…”
Section: The Benefits Of Empathy For Patients and Physiciansmentioning
confidence: 99%
“…Done appropriately, empathic and reassuring behaviour can help to decrease anxiety, relieve distress, increase therapeutic rapport, and improve patient satisfaction and health outcomes (Derksen et al, 2013;Norfolk et al, 2007;O'Grady, 2011).…”
Section: Approachability Featuresmentioning
confidence: 99%